Non-antibiotic strategies for prevention and treatment of internalized Staphylococcus aureus - Li, Jiangbi; Wen, Qiangqiang; Gu, Feng; An, Lijuan; Yu, Tiecheng (Frontiers in Microbiology, 2022)
Staphylococcus aureus (S. aureus) infections are often difficult to cure completely. One of the main reasons for this difficulty is that S. aureus can be internalized into cells after infecting tissue. Because conventional antibiotics and immune cells have difficulty entering cells, the bacteria can survive long enough to cause recurrent infections, which poses a serious burden in healthcare settings because repeated infections drastically increase treatment costs. Therefore, preventing and treating S. aureus internalization is becoming a research hotspot. S. aureus internalization can essentially be divided into three phases: (1) S. aureus binds to the extracellular matrix (ECM), (2) fibronectin (Fn) receptors mediate S. aureus internalization into cells, and (3) intracellular S. aureus and persistence into cells. Different phases require different treatments.. Many studies have reported on different treatments at different phases of bacterial infection. In the first and second phases, the latest research results show that the cell wall-anchored protein vaccine and some microbial agents can inhibit the adhesion of S. aureus to host cells. In third phase, some drugs inhibiting the NF-kB pathway can prevent bacteria from entering cells. More importantly, nanoparticles, photochemical internalization, cell penetrating peptides, antimicrobial peptides, and bacteriophage therapy can effectively eliminate bacteria from cells. In this paper, the recent progress in the infection process, the prevention and treatment of S. aureus internalization is summarized by reviewing a large number of studies.